2008
DOI: 10.1524/zkri.2008.1099
|View full text |Cite
|
Sign up to set email alerts
|

The Co–Ni distribution in decagonal Al69.7(4)Co10.0(4)Ni20.3(4)

Abstract: Abstract. The Co--Ni distribution in d-Al 69.7(4) Co 10.0(4) Ni 20.3(4) was investigated based on X-ray and neutron diffraction data. The structure was modelled in higher dimensional space using the 'charge-flipping' and 'low-density elimination' methods and it was quantitatively refined in three-dimensional space employing a pseudo-approximant approach. In higher-dimensional description, the Co atoms are found at the centre of one of the two symmetry independent occupation domains, enclosed by regions mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
3
1
Order By: Relevance
“…Also, the present chemical ordering, in which TM atoms forming the 0.76 nm pentagonal tiling and ones in MSs located at special positions in the 0.76 nm pentagonal tiling are different kinds of TM atoms, supports the justification of the new models. It should be noticed finally that Co atom positions determined from the present study are different from those proposed by X-ray and neutron diffraction in an Al 69.7 Co 10.0 Ni 20.3 DQCs [24]. In the result by the diffraction analysis, Co atoms are mainly located at vertices of pentagonal tiling with a bond length of 1.2 nm.…”
Section: Summary and Discussioncontrasting
confidence: 93%
“…Also, the present chemical ordering, in which TM atoms forming the 0.76 nm pentagonal tiling and ones in MSs located at special positions in the 0.76 nm pentagonal tiling are different kinds of TM atoms, supports the justification of the new models. It should be noticed finally that Co atom positions determined from the present study are different from those proposed by X-ray and neutron diffraction in an Al 69.7 Co 10.0 Ni 20.3 DQCs [24]. In the result by the diffraction analysis, Co atoms are mainly located at vertices of pentagonal tiling with a bond length of 1.2 nm.…”
Section: Summary and Discussioncontrasting
confidence: 93%
“…A similar coordination has been reported for Co in o-Co 4 Al 13 (Grin et al, 1994). The similarity of Rh and Co is also recalled from EXAFS (Zaharko et al, 2001) and neutron diffraction studies (Weber et al, 2008) made on Ni-rich d-Al-Ni-Co for which both the techniques confirm Co pentagonal coordination with Al. The other two types of clusters commonly met in decagonal quasicrystals (Steurer, 2004) are identified around partly occupied sites at the center (Fig.…”
Section: Local Atomic Environmentssupporting
confidence: 77%
“…In contrast to d-Al-Ni-Co, where the close values for X-ray atomic scattering factors [f Ni (0) = 28, f Co (0) = 27] make those elements difficult to distinguish by X-ray diffraction, the distribution of the TM atoms can be easily determined in the case of d-Al-Ni-Rh [f Rh (0) = 45]. While the Ni/Co distribution in d-Al-Ni-Co had to be studied by other techniques such as neutron scattering (Weber et al, 2008) and polarized EXAFS (Zaharko et al, 2001) requiring large single crystals, in the case of d-Al-Ni-Rh this can be done on small crystals by X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…Averaging of several successful CF or LDE runs can drastically improve the quality of structure solutions (Wu et al, 2004;Katrych et al, 2007;Weber et al, 2008) and may be done either in real space, by averaging the electron densities, or in reciprocal space, by averaging the resulting structure factors of n single runs with different random number generator seeds by applying…”
Section: Data Averagingmentioning
confidence: 99%
“…CF and LDE have proven particularly useful in the field of modulated structures and quasicrystals (QCs). In their higher-dimensional description, where no powerful standard structure solution methods were available before, CF and LDE work well and provide excellent structure solutions Palatinus, 2004;Katrych et al, 2007;Weber et al, 2008). For periodic structures it was shown that the CF algorithm was able to solve complex metallic structures with giant unit cells with more than 23 000 atoms (Weber et al, 2009), as well as several protein structures with diffraction data of atomic resolution (Dumas & van der Lee, 2008).…”
Section: Introductionmentioning
confidence: 99%